Economic Policies and Intimate Partner Violence Prevention: Emerging Complexities in the Literature. Issue 21 (November 2018) - Tankard, Margaret E.; Iyengar, Radha
Although the question of whether economic policies serve to reduce rates of intimate partner violence (IPV) has long been raised, rigorous tests of this question have only begun to take place recently. Given the mixed evidence to date, much remains unknown about the circumstances in which a positive or negative relationship holds between changes in financial well-being and IPV. We describe an empirically based theoretical model that may link economic empowerment to IPV and that highlights research questions for further testing. This model reflects two theoretical pathways through which economic policies may reduce IPV: A program may activate social and psychological empowerment as protective factors and a program may deactivate cognitive and behavioral risk factors such as stress and substance abuse. We then consider the relevance of each of a range of economic policies and review existing experimental evidence regarding the effect of such programs on IPV. We discuss unconditional and conditional cash transfers, savings programs, microfinance and income generation programs, and economic programs combined with relationship-related training. Gaps in research on this topic and emerging complexities in the literature suggest the following three key areas that would benefit from greater research and evaluation: comparison across programs based on size and design, assessment of the returns to economic empowerment of young adults, and more evaluations in high-income countries.